Protecting the Mbau Komodo in Riung, Flores: Local Adat, National Conservation and Ecotourism Developments - Halia Asriyani; Bart Verheijen (Forestry Faculty, Universitas Hasanuddin, 2020)
The Komodo dragon is one of the most exotic animals of the Wallacea region. Conservation efforts aimed at protecting the Komodo dragon and the unique biodiversity in the region have created a particularly strained relationship between state interests, local livelihood and tourism developments. This article examines recent antagonisms between national agencies, local interests and livelihoods by describing a unique and relatively unknown case study: the Riung Subdistrict and Sambinasi Village and the protection of the Komodo dragons by the local Baar community. Based on information from 19 qualitative in-depth interviews, and the analysis of a recent local Adat meeting in March 2019, this article shows that the Baar were successful in reclaiming land from the national conservation agencies. Meanwhile, they simultaneously formulated new local customary rules on how to treat the Komodo dragon, hence reclaiming ownership over conservation rules and empowering local institutions. Recently, all parties have subscribed to a new ecotourism agenda for further development of the area. This agenda might reshape relations between national agencies and the local communities, as conservation is increasingly linked to new forces of global tourism.